Signal Detection for Cardiovascular Adverse Events of DPP-4 Inhibitors Using the Korea Adverse Event Reporting System Database, 2008–2016 - Yi, Hyemin; Lee, Ji-Ho; Shin, Ju-Young (Yonsei medical journal, 2019)
Cardiovascular adverse events (AEs) after use of dipeptidyl peptidase-4 (DPP4) inhibitors have been reported and suspected since the launch of DPP-4 inhibitors in 2006. However, few studies have investigated the association between cardiovascular AEs and DPP-4 inhibitors. The objective of this study is to detect the signals of cardiovascular AEs after use of DPP-4 inhibitors by analyzing the Korea Institute of Drug Safety & Risk Management-Korea Adverse Event Reporting System Database (KIDS-KD). Data on the use of oral antidiabetic drugs from 2008 to 2016 were extracted from KIDS-KD, and analyzed descriptively. Data mining was conducted by calculating three indices, which were proportional reporting ratios, reporting odds ratios, and information components, to detect signals from use of all oral antidiabetic drugs including DPP-4 inhibitors. Then, the suspected adverse drug reactions (ADRs) were confirmed by signal detection, and drug label information between the Korea Ministry of Food and Drug Safety and the U.S. Food and Drug Administration were compared. Cardiovascular AEs after taking DPP-4 inhibitors were detected in only three (1.0%) out of a total of 307 AE reports. Two of the three cardiovascular AEs were reported after using sitagliptin and one using gemiglipitin, but these were not statistically significant. Analysis of spontaneous ADR reports data on the use of DPP-4 inhibitors could not showed the association between DPP-4 inhibitors and cardiovascular AEs, due to a small number of cardiovascular AEs reports.